2020
DOI: 10.1002/adma.202000508
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Enhanced Polarization Switching in the Improper Ferroelectric LuFeO3

Abstract: Results of switching behavior of the improper ferroelectric LuFeO3 are presented. Using a model set of films prepared under controlled chemical and growth‐rate conditions, it is shown that defects can reduce the quasi‐static switching voltage by up to 40% in qualitative agreement with first‐principles calculations. Switching studies show that the coercive field has a stronger frequency dispersion for the improper ferroelectrics compared to a proper ferroelectric such as PbTiO3. It is concluded that the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 54 publications
3
31
1
Order By: Relevance
“…On the other hand, the broad reflections unveiled for the doped LMFO indicate smaller size crystallites. Rietveld refinements of the XRD data (not shown here) reveal that LMFO, BLMFO and CLMFO adopt an orthorhombic (Pnma) structure while a rhombohedral structure (R-3c) is obtained for the SLMFO compound in partial accordance with previous reports 19,21 . Shaheen et al reported an orthorhombic perovskite structure, but with space group Pbnm for BLMFO and CLMFO, while a rhombohedral structure (space group R-3c) for SLMFO was observed 19 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the broad reflections unveiled for the doped LMFO indicate smaller size crystallites. Rietveld refinements of the XRD data (not shown here) reveal that LMFO, BLMFO and CLMFO adopt an orthorhombic (Pnma) structure while a rhombohedral structure (R-3c) is obtained for the SLMFO compound in partial accordance with previous reports 19,21 . Shaheen et al reported an orthorhombic perovskite structure, but with space group Pbnm for BLMFO and CLMFO, while a rhombohedral structure (space group R-3c) for SLMFO was observed 19 .…”
Section: Resultssupporting
confidence: 90%
“…shows the zero-field cooled (ZFC) magnetization as a function of temperature measured under an applied magnetic field of 0.2 T for undoped and doped LMFO. The measured magnetization curve of LMFO is similar to that reported by Barrozo et al21 . A broad transition centered around 80 K is observed for LMFO, presumably from a ferromagnetic (FM) to a paramagnetic (PM) phase.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…3(b) and fit with the two aforementioned models. The fitting with the power law gave the value of the exponent, β = 0.28, which is higher than that reported in h-ErMnO3 bulk single crystals (β ≈ 0.1) 9 but lower than the value reported in h-LuFeO3 thin films (β ≈ 0.66) 10 . On the other hand, from the Du-Chen model, a cutoff frequency of ~ 365 kHz was obtained which is lower than that in PZT thin films (1~2 MHz) 31 , but similar to that in barium strontium titanate (BST) thin films 32 .…”
Section: Resultscontrasting
confidence: 55%
“…However, although the electrostatic effects may not quench the primary structural distortion, their effects on the spontaneous polarization have not been properly addressed. In addition, an understanding of the polarization switching mechanism is of vital importance for any technological applications 9,10 . The difficulty in growth and electrical characterization of ultrathin films on structurally mismatched substrates, coupled with the intertwined interfacial and electrostatic effects, might have contributed to the lack of systematic studies in this regard.…”
Section: Introductionmentioning
confidence: 99%